Ensure Your Fleet is Always Operating at its Top Efficiency Using Advanced Monitoring and Benchmarking Technology - Kinnane T; Rogers R (The Australasian Institute of Mining and Metallurgy, 1994)
In a typical open cast mining operation, investigation of how existing truck performance compares with the highest achievable truck performance is largely neglected. This paper addresses this issue by proposing a computerised system that will provide a systematic method for comparing existing truck operational performance to the highest performance considered achievable. Through analyses of existing versus achievable performances, various inefficiencies associated with truck operations can be identified. These inefficiencies could occur due to machine configurations, haul route design and conditions or operator skill level. Remedial action should then be taken in a timely fashion to better manage these factors and to ensure the fleet is always operating at its peak efficiency.